An algorithm combining VVSYmQ® and VCSS scores may help to predict disease severity in C2 patients. (December 2021) - Sadek, Mikel; Pergamo, Matthew; Almeida, Jose I; Jacobowitz, Glenn R; Kabnick, Lowell S
Objectives: The purpose was to assess whether combining patient reported scores (VVSymQ®) and physician reported scores (VCSS) stratifies disease severity in C2 patients. Methods: Consecutive patients were pooled from the VANISH-1 and VANISH-2 cohorts. VCSS and VVSymQ® were calculated for each patient. The relationship between scoring systems was evaluated using Pearson's correlation and frequency distribution analysis. Results: Two-hundred and ten C2 limbs were included. Scoring systems demonstrated: VVSymQ®: mean = 8.72; VCSS: mean = 6.32; correlation (r = 0.22, p = 0.05). Frequency distribution analysis demonstrated 61.4% of patients had low VVSymQ® and low VCSS; 31.3% had elevated VVSymQ® and increased VCSS; 7.3% were inconsistent with C2 disease. Strict concordance analysis revealed 40.5% had VVSymQ® (< 9)/VCSS (0-6), 18.6% had VVSymQ® (≥ 9)/VCSS (7-9), and 2.9% had VVSymQ® (≥9)/VCSS (≥10). Conclusions: For combined elevated VVSymQ® and VCSS, moderate/severe disease is corroborated, and intervention may be indicated. For combined lower scores, the disease severity is mild and conservative therapy is more appropriate.